Flouting Maxims in the main characters of UP! animated movie - Burhan, Sarah Rosalina (Jurnal Ilmiah Mahasiswa FIB, 2013)
This study is design to find out what the maxims flouted by the main characters on the animated movie  UP!  and to find out the intended meanings of the utterances being flouted by the main characters on the animated movie UP! This study not only to know what the maxims are flouted but also to know why people do flouting maxims in their communication. The data source of this study is taken from UP!’s subtitle that was obtained from the internet and the data of this study are the utterances of the main characters that are flouted. The researcher only looks for the utterances that are flouting the maxims. The results of this study found that there were 47 dialogues containing flouting maxims in UP!  animated movie. That consists of four kinds flouting maxims, namely flouting maxim of quality, flouting maxim of quantity, flouting maxim of manner, and flouting maxim of relevant. The purposes of flouting the maxims were to make the main characters are comfortable in the conversation, to avoid other questions, to show pleasure or anger, and to show their knowledge on something in this movie.Key word: Cooperative Principles, Flouting Maxims, Intended Meanings, UP! animated movie.